Pemenuhan Hak Politik Warga Negara Oleh Komisi Pemilihan Umum (KPU) Kota Banjarmasin (Studi Kasus Penyandang disabilitas) - Fahlevi, Reja; Rahman, Budi (Academy of Education Journal, 2024)
Political rights for people with disabilities are one component of Human Rights that must be fulfilled. However, if you look at the reality today, there are still many political rights for people with disabilities that are not fulfilled. The aim of this research is to see and analyze the form of fulfillment of political rights regarding socialization for people with disabilities and the form of provision of infrastructure and facilities by the General Election Commission (KPU) of Banjarmasin City. This research uses descriptive qualitative methods by conducting interviews and observations. The results of this research show that the Banjarmasin City KPU fulfills the Political Rights of Persons with Disabilities in two ways. First, by providing interpreters for deaf people in outreach activities regarding procedures and mechanisms related to general elections. Second, the provision of facilities and infrastructure for blind people with disabilities is provided with braille aids in elections. and providing wheelchair access and friendly services for people with disabilities in Banjarmasin City.